If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.9(y + 1.4) = -1.8 Reorder the terms: 0.9(1.4 + y) = -1.8 (1.4 * 0.9 + y * 0.9) = -1.8 (1.26 + 0.9y) = -1.8 Solving 1.26 + 0.9y = -1.8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.26' to each side of the equation. 1.26 + -1.26 + 0.9y = -1.8 + -1.26 Combine like terms: 1.26 + -1.26 = 0.00 0.00 + 0.9y = -1.8 + -1.26 0.9y = -1.8 + -1.26 Combine like terms: -1.8 + -1.26 = -3.06 0.9y = -3.06 Divide each side by '0.9'. y = -3.4 Simplifying y = -3.4
| -8t=n+v | | f(x)=2x^2+4x+1.5 | | -8(-7-5n)=-32-4n | | 13j+52=1 | | 8x=14+1x | | -59=5(1-8x)-7(1-3x) | | 21=15-r | | 30*15=x | | 3+9n=22 | | 5(3x+7)=3(7+8x) | | 3(8+6v)+8=-40+6v | | 4(1-7a)=88 | | 10c^2+29c-21=0 | | 11m+13=m+24 | | 9j+5=67 | | 90=5(-2-5n) | | 20y^2+17y+3= | | 7-3x=x+-4(2+x) | | x^2+14x-182=0 | | 9j+5=30 | | 2(-8x+6)=-84 | | -7(2x+8)=-126 | | 9=17u-8u | | 10v^2+43v-9=0 | | 5x-18=2(4x-15) | | 9+5=67 | | 3xy+2y+1=5+6y | | ln(y)=ln(x+C) | | -2x-23=-19 | | Y^2+3y=4y-6 | | 8(r+7)=88 | | 2n-(14-n)=1 |